2020
DOI: 10.1609/icaps.v30i1.6739
|View full text |Cite
|
Sign up to set email alerts
|

PDDLStream: Integrating Symbolic Planners and Blackbox Samplers via Optimistic Adaptive Planning

Abstract: Many planning applications involve complex relationships defined on high-dimensional, continuous variables. For example, robotic manipulation requires planning with kinematic, collision, visibility, and motion constraints involving robot configurations, object poses, and robot trajectories. These constraints typically require specialized procedures to sample satisfying values. We extend PDDL to support a generic, declarative specification for these procedures that treats their implementation as black boxes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Similarly, the method in (Dantam et al 2016) incrementally incorporates information about the motion feasibility into the symbolic description by using a constraint-based task planning formulation and a Satisfiability Modulo theory (SMT) solver. Another related approach is PDDLStream (Garrett, Lozano-Pérez, and Kaelbling 2020), which also combines symbolic planners with motion planning. Specifically, PDDLStream uses constrained samplers (in configuration space) to discretize the motion planning problem, and PDDL planning to solve the combined problem.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the method in (Dantam et al 2016) incrementally incorporates information about the motion feasibility into the symbolic description by using a constraint-based task planning formulation and a Satisfiability Modulo theory (SMT) solver. Another related approach is PDDLStream (Garrett, Lozano-Pérez, and Kaelbling 2020), which also combines symbolic planners with motion planning. Specifically, PDDLStream uses constrained samplers (in configuration space) to discretize the motion planning problem, and PDDL planning to solve the combined problem.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, we do not compare to other methods in task and motion planning, e.g. (Garrett, Lozano-Pérez, and Kaelbling 2020), that use different underlying problem formulations and methods.…”
Section: Baselinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmitt et al [16] offer almost-surely asymptotically optimal manipulation planning based on a precomputed roadmap and domain-specific samplers for mode transitions. Garrett et al [17] produce TMP solutions that are optimal in symbolic action cost, but assume domain-specific samplers and do not jointly optimize their motions and action parameter choices. Recent results [5] have shown that almost-sure asymptotic optimality results from pure motion planning are preserved for multimodal TMP under realistic assumptions on the measure of mode transition sets.…”
Section: B Almost-surely Asymptotically Optimal Tmpmentioning
confidence: 99%
“…TMP solvers adapt advances in standalone symbolic planning to the TMP context [1,17,19,20]. Symbolic planning for TMP is uniquely challenging since valid symbolic plans may not correspond to valid motion plans.…”
Section: Symbolic Planning For Tmpmentioning
confidence: 99%